(untitled) (JURNAL ADMINISTRASI PUBLIK, 2017)
ABSTRACT: Although the discipline rules of civil servent is dearly and distinct define the obligations and probubitions, but the fact shows that there still a lot of discipline violations done by the civil servent. The purpose of this research is to find out the influence of discipline on employee’s work achievement of the social services in district of West Halmahera. The type of this research is exploratory research with quantitative approach. The research sample are 35 respondents drawn by random at the social services in district of west Halmahera. For the data collection used questionnaire and interview technique. The data analysis tehniques used statistic analysis of linear reqression and product moment correlation. Based on the data analysis is thengwen coclusions as follows : (1). The discipline has a funcional relationship or positive influence and significant as wel as shape or linear pattern on employee’s work achievement of the social services in district of west Halmahera. That, the increasing of the work achievement. (2). The discipline has a correlation and the significant determination forwards the development on employee’s work achievement of the social services in district of west Halmahera. That, the more discipline, the more it gets achievement. Based on the conclusions is then developed some suggestions as follows : (a). The preventive discipline needs to be improved on employee’s of the social services in district of west Halmahera. For that, the coaching of discipline is necessary to do continuously. (b). The repressive discipline needs to applying for the employee’s who violate the rules of discipline. For that the punishment of discipline should be done consistenly. Keyword : Discipline, work achievement